2015
DOI: 10.1039/c5ob01633a
|View full text |Cite
|
Sign up to set email alerts
|

An internal charge transfer-dependent solvent effect in V-shaped azacyanines

Abstract: a New V-shaped non-centrosymmetric dyes, possessing a strongly electron-deficient azacyanine core, have been synthesized based on a straightforward two-step approach. The key step in this synthesis involves palladium-catalysed cross-coupling of dibromo-N,N'-methylene-2,2'-azapyridinocyanines with arylacetylenes. The resulting strongly polarized π-expanded heterocycles exhibit green to orange fluorescence and they strongly respond to changes in solvent polarity. We demonstrate that differently electron-donating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The same group also reported the synthesis and study of the optical properties of two bis(styryl)-azacyanines. 21 In this case, the combination of high two-photon absorption cross sections and strong fluorescence QY resulted in good two-photon brightness which opened up the possibility of the use of these dyes as bioimaging agents.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same group also reported the synthesis and study of the optical properties of two bis(styryl)-azacyanines. 21 In this case, the combination of high two-photon absorption cross sections and strong fluorescence QY resulted in good two-photon brightness which opened up the possibility of the use of these dyes as bioimaging agents.…”
Section: Introductionmentioning
confidence: 98%
“…All these findings revealed that the photophysical properties of azacyanines can explicitly be controlled via the substitution of electron-donating/withdrawing groups. The same group also reported the synthesis and study of the optical properties of two bis­(styryl)-azacyanines . In this case, the combination of high two-photon absorption cross sections and strong fluorescence QY resulted in good two-photon brightness which opened up the possibility of the use of these dyes as bioimaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…Organic ICT compounds are ideal candidates as third-order nonlinear optical materials because of their inherent high hyperpolarizabilities [35][36][37]. Among these molecules, the quadrupolar D-π-A-π-D structure is highlighted for its excellent nonlinear optical properties [38][39][40][41], with large twophoton absorption (TPA) cross-sections [42,43]. The intramolecular charge transfer, which occurs in systems containing both donor and acceptor parts, will influence the TPA properties strongly [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…In the chemistry of dyes and pigments, systems with extended π-conjugation have prevailed in the literature for years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. There is, however, an increased interest in weakly coupled systems containing multiple biaryl linkages [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%